The complete mitochondrial genome of the bambusicolous fungus Fusarium bambusae (Nectriaceae, Ascomycota) - Xin-Cun Wang; Zhao-Qing Zeng; Wen-Ying Zhuang (Mitochondrial DNA. Part B. Resources, 2018)
The complete nucleotide sequence of the mitochondrial genome of the bambusicolous fungus Fusarium bambusae was determined using the next-generation sequencing technology. The circular molecule is 63,593 bp long with a GC content of 31.92%. Gene prediction revealed 44 genes encoding 15 conserved proteins, 27 tRNAs, and the large and small ribosomal RNAs. All genes are located on the same strand. The tRNA genes contain codons for all 20 standard amino acids. It turns out to be similar to the previously sequenced mitochondrial genomes of Fusarium circinatum and F. verticillioides. The differences lie in the number of introns embodied in protein-coding genes. Four introns exist in the mitochondrial genome of F. verticillioides, 10 in F. bambusae, and 14 in F. circinatum. The phylogenetic analysis confirmed F. bambusae as a member of Fusarium (Nectriaceae). The mitochondrial genome of F. bambusae will contribute to the understanding of phylogeny and evolution of the genus and family.